2018
DOI: 10.1093/gbe/evy253
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Copy Number at the MHC Varies across the Avian Tree of Life

Abstract: The evolution of the major histocompatibility complex (MHC) is shaped by frequent gene duplications and deletions, which generate extensive variation in the number of loci (gene copies) between different taxa. Here, we collected estimates of copy number at the MHC for over 250 bird species from 68 families. We found contrasting patterns of copy number evolution between MHC class I and class IIB, which encode receptors for intra- and extracellular pathogens, respectively. Across the avian evolutionary tree, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 70 publications
5
134
1
2
Order By: Relevance
“…As tightly linked MHC loci often co-segregate, investigations of the structure of MHC genes, haplotypes, and recombination between MHC loci may improve our understanding of correlations between MHC variation, fitness, and disease in wild populations . The MHC exhibits extraordinary evolutionary dynamics with rapid expansions and contractions of MHC gene copy number, and substantial variation in MHC sequence and haplotype structure (Kelley, Walter, & Trowsdale, 2005;Minias et al, 2018;Masatoshi Nei & Rooney, 2005;O'Connor et al, 2016;Ohta, 1991;Spurgin et al, 2011). Thus, previous studies have reported considerable variation in the number of different MHC alleles between individuals within species, suggesting that MHC gene copy number variation may be a common trait, at least among birds (Biedrzycka, O'Connor, et al, 2017;Gaigher et al, 2016;Roved et al, 2018;Stervander, Dierickx, Thorley, Brooke, & Westerdahl, 2020;Whittingham, Dunn, Freeman-Gallant, Taff, & Johnson, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As tightly linked MHC loci often co-segregate, investigations of the structure of MHC genes, haplotypes, and recombination between MHC loci may improve our understanding of correlations between MHC variation, fitness, and disease in wild populations . The MHC exhibits extraordinary evolutionary dynamics with rapid expansions and contractions of MHC gene copy number, and substantial variation in MHC sequence and haplotype structure (Kelley, Walter, & Trowsdale, 2005;Minias et al, 2018;Masatoshi Nei & Rooney, 2005;O'Connor et al, 2016;Ohta, 1991;Spurgin et al, 2011). Thus, previous studies have reported considerable variation in the number of different MHC alleles between individuals within species, suggesting that MHC gene copy number variation may be a common trait, at least among birds (Biedrzycka, O'Connor, et al, 2017;Gaigher et al, 2016;Roved et al, 2018;Stervander, Dierickx, Thorley, Brooke, & Westerdahl, 2020;Whittingham, Dunn, Freeman-Gallant, Taff, & Johnson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The use of family data to infer segregating MHC haplotypes offers a powerful method to overcome these challenges (Gaigher et al, 2016(Gaigher et al, , 2018. However, for such studies to capture a significant part of the MHC haplotype variation in wild populations, segregation patterns should be analyzed in a large number of families -especially when studying species with high levels of MHC diversity, such as songbirds (clade Passeri of Passeriformes) (Minias, Pikus, Whittingham, & Dunn, 2018;O'Connor, Strandh, Hasselquist, Nilsson, & Westerdahl, 2016). Fortunately, as the cost of high-throughput DNA sequencing continues to decrease, genotyping the number of samples necessary to infer MHC haplotypes in a large number of families is becoming feasible to many research groups.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the theoretical framework of a trade‐off between recognizing a broad array of pathogens, and increased depletion of circulating T‐cells following negative selection in the thymus and risk of autoimmune diseases with increased number of MHC alleles (e.g., Gough & Simmonds, ; Nowak et al, ; Woelfing et al, ). What level of intraindividual MHC diversity that constitutes the optimum might vary among species due to ecological differences, e.g., according to the pathogen load experienced (Minias et al, ; O'Connor, Cornwallis, Hasselquist, Nilsson, & Westerdahl, ; Westerdahl et al, ). This implies that the more pathogens a species is exposed to, the stronger the selective force for increased diversity will be, driving the optimum towards a higher diversity.…”
Section: Discussionmentioning
confidence: 99%
“…We restricted our analyses to MHCII. The bluethroat has relatively few MHCI loci (i.e., four; O'Connor, Strandh, Hasselquist, Nilsson, & Westerdahl, 2016;Rekdal et al, 2018), which might be due to less exposure to intra-than extracellular pathogens (Minias et al, 2018) or some compensatory immunological mechanism (e.g., Gangoso et al, 2012;Star et al, 2011). Recent studies have identified a link between MHCII composition and individual odor in birds, possibly mediated through microbial communities and uropygial gland secretions (Leclaire et al, 2019(Leclaire et al, , 2014Leclaire, Strandh, Mardon, Westerdahl, & Bonadonna, 2017;Slade et al, 2016;Strandh et al, 2012).…”
Section: Intermediate Not Maximized Mhcii Diversitymentioning
confidence: 99%
See 1 more Smart Citation